2007
DOI: 10.1038/sj.bjc.6603589
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and incidence of second cancers following treatment for testicular cancer

Abstract: We studied 5555 seminoma patients and 3733 patients with nonseminomatous testicular cancers diagnosed in Southeast England between 1960 and 2004. For both groups survival improved over time: 10-year relative survival increased from 78% in 1960 -1969 to 99% in 1990 -2004 for seminomas, and from 55 to 95% for nonseminomas. In the early period mortality was still significantly increased more than 15 years after diagnosis in both groups, whereas in more recent periods the excess deaths mainly occurred in the fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
24
0
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(32 citation statements)
references
References 23 publications
5
24
0
3
Order By: Relevance
“…After chemotherapy the risk includes leukaemias, lung cancer, and melanoma. 43 There is also an increased risk of cardiac events. A cohort study of UK survivors found a relative risk of cardiovascular disease of 2.6 after chemotherapy and 2.4 after radiotherapy.…”
Section: What Are the Side Effects Of Combination Chemotherapy?mentioning
confidence: 99%
“…After chemotherapy the risk includes leukaemias, lung cancer, and melanoma. 43 There is also an increased risk of cardiac events. A cohort study of UK survivors found a relative risk of cardiovascular disease of 2.6 after chemotherapy and 2.4 after radiotherapy.…”
Section: What Are the Side Effects Of Combination Chemotherapy?mentioning
confidence: 99%
“…However, survivors of both testicular cancer and Hodgkin lymphoma are at increased risk of second solid malignancies, beginning 10-15 years after diagnosis (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). Gastrointestinal cancer, especially stomach cancer, accounts for the larger part of second solid malignancies among testicular cancer survivors.…”
Section: Introductionmentioning
confidence: 98%
“…Fortunately, the mortality rate has been progressively decreasing over time as a result of early diagnosis and the advancements made in treatment protocols [1,3]. Specifically, the coadministration of bleomycin, etoposide, and cis-platinum (BEP) has improved the 5-yr survival rate of testis cancer patients to over 90%, for all stages of testicular germ cell tumors [4][5][6].…”
Section: Introductionmentioning
confidence: 99%